Design, Synthesis, Molecular Docking and In vitro Biological Evaluation of Benzamide Derivatives as Novel Glucokinase Activators - Kazi, A.A.; Chatpalliwar, V.A. (Current Enzyme Inhibition, 2022)
Background: Glucokinase (GK) is a cytoplasmic enzyme that metabolizes glucose to glucose- 6-phosphate and supports adjusting blood glucose levels within the normal range in humans. In pancreatic β-cells, it plays a leading role in governing the glucose-stimulated secretion of insulin, and in liver hepatocyte cells, it controls the metabolism of carbohydrates. GK acts as a promising drug target for treating patients with type 2 diabetes mellitus (T2DM). Objectives: The present work has been designed to discover some novel substituted benzamide derivatives. Methods: This work involved designing novel benzamide derivatives and their screening by docking studies to determine the binding interactions for the best-fit conformations in the binding site of the GK enzyme. Based on the results of docking studies, the selected molecules were synthesized and tested for in vitro GK enzyme assay. The structures of newly synthesized products were confirmed by IR, NMR, and mass spectroscopy. Results: Amongst the designed derivatives, compounds 4c, 4d, 4e, 5h, 5j, 5l, 5m, 5n, 5p, and 5r have shown better binding energy than the native ligand present in the enzyme structure. The synthesized compounds were subjected to in vitro GK enzyme assay. Out of all, compounds 4c, 4d, 5h, 5l, and 5n showed more GK activation than control. Conclusion: From the present results, we have concluded that the synthesized derivatives can activate the human GK enzyme effectively, which can be helpful in the treatment of T2DM.
Keywords: 1V4S